Gain a child, lose a tooth?: using natural experiments to distinguish between fact and fiction - Gabel, Frank; Jürges, Hendrik; Kruk, Kai Eberhard; Listl, Stefan (Journal of epidemiology and community health, 2018)
Background Dental diseases are among the most frequent diseases globally and tooth loss imposes a substantial burden on peoples' quality of life. Non-experimental evidence suggests that individuals with more children have more missing teeth than individuals with fewer children, but until now there is no causal evidence for or against this. Methods Using a Two-Stage Least Squares (2SLS) instrumental variables approach and large-scale cross-sectional data from the Survey of Health, Ageing, and Retirement in Europe (study sample: 34 843 non-institutionalised individuals aged 50+from 14 European countries and Israel study years: 2015), we investigated the causal relationship between the number of biological children and their parents’ number of missing natural teeth. Thereby, we exploited random natural variation in family size resulting from (i) the birth of multiples vs singletons, and (ii) the sex composition of the two first-born children (increased likelihood of a third child if the two first-born children have the same sex). Results 2SLS regressions detected a strong causal relationship between the number of children and teeth for women but not for men when an additional birth was given after the first two children had the same sex. Women then had an average of 4.27(95%-CI: 1.08 to 7.46) fewer teeth than women without an additional birth whose first two children had different sexes. Conclusions This study provides novel evidence for causal links between the number of children and the number of missing teeth. An additional birth might be detrimental to the mother’s but not the father’s oral health.